ANALYSIS STRATEGY FOR MAINTAINING THE LOCAL WISDOM IN TRYING MALAY HINTERLAND RUBBER FARMER IN THE BATANG CENAKU DISTRICT INDRAGIRI HULU REGENCY RIAU PROVINCE - Jahilin, Sunatra; Sayamar, Eri; Kausar, Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study are to identify local wisdom rubber plant has ever had (previously done but did not do it again now), formerly done by now they do the rubber farmers and which were not performed but is now made of rubber farmers. The method was used survey and Snowball Sampling in finding the respondent the right to obtain 15 respondents consisting of 1) Farmers Rubber, 2) Traditional Leaders, 3) Religious Leaders, 4) village officials, 5) Members farmer groups, 6) Collectors. Methods interviews were conducted to obtain information about local wisdom rubber plants. The criteria will be seeking respondents rubber farmers who have cultivated long experience and know the local wisdom rubber plants. The results showed that local wisdom rubber plant by the farmers in cultivation in 1) clearing of land that is numbered 15 indigenous 2) Nurseries are 4 local wisdom 3) Planting a total of 5 local wisdom 4) Maintenance numbered 11 local wisdom and 5) Rubber tapping totaling 12 indigenous 6) Rejuvenation totaled 4 indigenous 7) Processed Material totaled 3 lokal wisdom 8) Marketing amounted to 3 lokal wisdom. Total indigenous rubber plant at 58 local wisdom. Strategies in maintaining local knowledge of rubber cultivation in the Districts Batang Cenaku gained 9 strategy, which gained 3 SO strategy, ST there are 2 strategies, WO 2 and WT strategy 2 strategy. Keywords: Local Wisdom, Rubber Plant, Rubber Farmers, Formerly, Now PENDAHULUAN Pembangunan pertanian merupakan bagian dari pembangunan nasional yang memegang peran penting dari keseluruhan perekonomian nasional, hal ini dikarenakan sektor pertanian mampu memberikan pemasukan untuk negara berupa devisa (diekspor). Dewasa ini pembangunan sektor pertanian lebih dititikberatkan pada subsektor perkebunan, karena subsektor perkebunan memiliki potensi yang bagus untuk dikembangkan. Karet merupakan salah satu